18F-FDG-PET correlates of cognitive impairment in ALS. (5th January 2016) - Canosa, Antonio; Pagani, Marco; Cistaro, Angelina; Montuschi, Anna; Iazzolino, Barbara; Fania, Piercarlo; Cammarosano, Stefania; Ilardi, Antonio; Moglia, Cristina; Calvo, Andrea; Chiò, Adriano
Abstract : Objective: To identify the metabolic signature of the various levels of cognitive deficits in amyotrophic lateral sclerosis (ALS) using 18 F-2-fluoro-2-deoxy-D-glucose-PET ( 18 F-FDG-PET). Methods: A total of 170 ALS cases consecutively enrolled at the ALS Center of Turin underwent brain 18 F-FDG-PET and were classified as displaying normal cognition (ALS-Cn; n = 94), full-blown frontotemporal dementia (ALS-FTD; n = 20), executive or nonexecutive cognitive impairment not fulfilling FTD criteria (ALS-Ci; n = 37), prevalent behavioral changes (n = 9), or nonclassifiable impairment (n = 10) according to neuropsychological testing. Group comparisons of 18 F-FDG-PET pattern were carried out among the cognitive subgroups. Results: We found a significantly reduced frontal and prefrontal metabolism in ALS-FTD as compared to ALS-Cn, while ALS-Ci showed an intermediate metabolic behavior in frontal cortex, being hypometabolic as compared to ALS-Cn, and relatively hypermetabolic as compared to ALS-FTD. Hypometabolism in frontal regions was associated in all comparisons to hypermetabolism in cerebellum, midbrain, and corticospinal tracts: the more severe the cognitive decline, the larger the size of the cluster and the statistical significance of 18 F-FDG uptake differences. Conclusions: This study demonstrated in a large cohort of patients with ALS a continuum of frontal lobe metabolic impairment reflecting the clinical and anatomic continuum ranging from pure ALS, through ALS with intermediate cognitive deficits, to ALS-FTD, and showing that patients with intermediate cognitive impairment display a characteristic metabolic pattern. Since 18 F-FDG-PET allows us to estimate the cerebral lesion load in vivo in neurodegenerative diseases, it might be helpful to investigate in ALS its association with neuropsychological testing along the disease course to disclose the early metabolic signature of possible cognitive impairment.